Cancer stem cells and mesenchymal stem cells in pancreatic ductal adenocarcinoma - V. O. Tumanskyi; I. S. Kovalenko (Patologìâ)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive types of cancer and chemotherapy resistant cancer, in the development of which poorly studied cancer stem cells (CSC) and mesenchymal stem cells (MSC) are of great importance. The purpose of the work is the analysis of the current literature data on the role of stem cells in the progression of PDAC. The stem cell pool of PDAC is heterogenic, consists of CSC and MSC, which form stem cell niches in the tumor. Three signaling molecular pathways play an important role in self-renewal and differentiation of pancreatic CSCs: Wnt, Sonic hedgehog and Notch. RSCs have the ability for self-renewal, for symmetric and asymmetric division, for partial differentiation, as well as for existence, self-renewal and differentiation outside the primary tumor. CSCs ensure growth and progression of the tumor, invasiveness and metastasis of PDAC, and also support its chemoresistance. MSCs of bone marrow origin in the pancreas are not involved in epithelial carcinogenesis, but when interacting with other cells of the microenvironment, exert a stimulating and inhibiting influence on the tumor. MSCs can act as promoters of oncogenesis through transformation into cancer-associated fibroblasts, local immunosuppression, stimulation of tumor neoangiogenesis, blockade of apoptosis of cancer cells, participation in the epithelial-mesenchymal transition and metastasis. MSCs can also act as suppressors of oncogenesis by stimulating the immuno-cellular infiltration of tumor tissue, suppressing the function of the AKT and Wnt signaling pathways, inducing cell cycle arrest and triggering cancer cell apoptosis, and suppressing tumor neoangiogenesis.Conclusion. CSCs play a key role in the implementation of the aggressive properties of PDAC; MSCs have an effect on both cancer stem cells and the actual cancer cells of PDAC, exerting both stimulating and inhibiting influence on the tumor. The available data on the role of MSCs in the progression of PDAC are still heterogeneous, which determines the relevance of further study of the issue.